PERBEDAAN LIKUIDITAS SAHAM SEBELUM DAN SESUDAH REVERSE STOCK SPLIT (STUDI EMPIRIS PADA BURSA EFEK INDONESIA) - FRANSISKA, LUSIANA; PURWANINGSIH, ANNA (Jurnal Ilmiah Akuntansi dan Bisnis, 2011)
This research aims to empirically study stock liquidity differences between before and after reverse stock split done by companies listed on Indonesia Stock Exchange. Liquidity is measured by means of Trading Volume Activity (TVA). To test the hypothesis nonparametric test, Wilcoxon test, is used. Nonparametric test is in use for the data that are not normally distributed. The result shows that there is a significant difference between stock liquidity before and after reverse stock split.
Keywords: stock liquidity, reverse stock split, trading volume activity